The Relationship between Leadership Styles and Conflict Management Strategies Used by Top and Middle Managers of Kerman\'s Educational Hospitals - mohammad nekoei moghadam; sajad delavari; mina salajeghe; mohammadhossein ghorbani (Tehran University of Medical Sciences, 2010)
Background: One of the necessities of hospital administrations is that the top and middle managers should be familiar with leadership styles and conflict management strategies completely and select a right managerial method. Through this, they can actively play a significant role in improving effectiveness and efficiency of hospital performance. The main objective of this research is surveying the relationship between Fidler's LPC score (as a sign for leadership style) and conflict management strategies (avoidance oriented, solution oriented, control oriented). Materials and Methods: For surveying leadership styles Fiddler's Least Preferred Coworker questionnaire and for surveying conflict management strategies, another questionnaire was used. The reliability of these two was 0.90 and 0.88 respectively. The survey population was consisted of the high and middle managers of Kerman's educational hospitals (81), and a sample 67 individuals was selected for survey. Results: The result showed that respondents mostly use communication oriented style and employed conflict management strategies are avoidance, solution and control respectively. Also it was observed that there is a positive and significant relation between LPC score and avoidance and solution strategies (r= 0.512 and 0.298 respectively). But there is a negative and significant relation between LPC score and control oriented strategy (r= -0.474). Conclusion: According to the findings it is suggested that, the reasons of using avoidance strategy should be surveyed and try to encourage people to state their inconsistent ideas and converse freely. This could help organization to improve its performance. But communication oriented style is suitable and its maintenance should be taken into consideration.